Unbiased next generation sequencing analysis confirms the existence of autosomal dominant Alport syndrome in a relevant fraction of cases. (17th October 2013) - Fallerini, C.; Dosa, L.; Tita, R.; Del Prete, D.; Feriozzi, S.; Gai, G.; Clementi, M.; La Manna, A.; Miglietti, N.; Mancini, R.; Mandrile, G.; Ghiggeri, G.M.; et al.
<x xml:space="preserve">Abstract</x> The mode of inheritance of Alport syndrome (ATS) has long been controversial. In 1927, the disease was hypothesized as a dominant condition in which males were more severely affected than females. In 1990, it was considered an X‐linked (XL) semidominant condition, due to COL4A5 mutations. Later on, a rare autosomal recessive (AR) form due to COL4A3/COL4A4 mutations was identified. An autosomal dominant (AD) form was testified more recently by the description of some large pedigrees but the real existence of this form is still questioned by many and its exact prevalence is unknown. The introduction of next generation sequencing (NGS) allowed us to perform an unbiased simultaneous COL4A3‐COL4A4‐COL4A5 analysis in 87 Italian families (273 individuals) with clinical suspicion of ATS. In 48 of them (55%), a mutation in one of the three genes was identified: the inheritance was XL semidominant in 65%, recessive in 4% and most interestingly AD in 31% (15 families). The AD form must therefore be seriously taken into account in all pedigrees with affected individuals in each generation. Furthermore, a high frequency of mutations (>50%) was shown in patients with only 1 or 2 clinical criteria, suggesting NGS as first‐level analysis in cases with a clinical suspicion of ATS.